The Effect of Operating Cash Flow, Sales Growth, and Operating Capacity on Financial Distress - Permaisita Anggun Sari; Omi Pramiana (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2025)
This research seeks to examine the impact of operational cash flow, sales growth, and operating capacity on financial distress within consumer cyclicals firms in the apparel and luxury goods sub-sector, listed on the Indonesia Stock Exchange for the period 2022–2024. This research employs a quantitative methodology utilizing an associative causal framework and secondary data derived from companies' yearly financial statements. We used SPSS software to do multiple linear regression to analyze the data. The results indicate that operating cash flow, sales growth, and operating capacity significantly influence financial distress, suggesting that enhanced cash flow production, sales performance, and asset utilization correlate with a diminished likelihood of financial difficulty. These results show that making a business better at making operating cash flow, keeping sales growth going, and using its assets more efficiently will help improve its financial situation and lower its financial stress. Descriptive data indicate that, on average, enterprises exhibit positive operating cash flow, continuous revenue growth, and an operating capacity over one, signifying operational efficiency and reasonably stable financial conditions. This study underscores the significance of proficient financial and operational management in sustaining financial stability and mitigating the risk of financial hardship in consumer cyclicals companies, especially within the apparel and luxury goods sub-sector.